IHWAL MENERJEMAHKAN: PROPOSISI TEORETIS CAKUPAN PENGKAJIAN DAN PENELITIAN - FX Nadar (Humaniora, 2005)
This paper argues that translation should be studied comprehensively in order to achieve optimal comprehension. The study of translation should be done comprehensively which includes the definition, process, principle, problems, management and linguistic aspects of translation. Research in translation should be related to the translation products, the previous learning experience of the translators, and the process of translation. Further, tools and facilities in doing a translation project should be taken into consideration.